2015
DOI: 10.1073/pnas.1517642113
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of constitutive cyclooxygenase-2 expression: Role of NF-κB and NFAT transcriptional pathways

Abstract: Cyclooxygenase-2 (COX-2) is an inducible enzyme that drives inflammation and is the therapeutic target for widely used nonsteroidal antiinflammatory drugs (NSAIDs). However, COX-2 is also constitutively expressed, in the absence of overt inflammation, with a specific tissue distribution that includes the kidney, gastrointestinal tract, brain, and thymus. Constitutive COX-2 expression is therapeutically important because NSAIDs cause cardiovascular and renal side effects in otherwise healthy individuals. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
117
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(134 citation statements)
references
References 33 publications
11
117
1
5
Order By: Relevance
“…Hence, constitutive neuronal PTGS2 transcription appears to be independent of NFB. This is in line with a recent study demonstrating both negligible constitutive NFB activity in brain and a lack of effect of NFB inhibition on PTGS2 promoter activity in knock-in reporter mice (21). Interestingly, stimulus-induced increases in neuronal COX-2 expression do appear to involve NFB binding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Hence, constitutive neuronal PTGS2 transcription appears to be independent of NFB. This is in line with a recent study demonstrating both negligible constitutive NFB activity in brain and a lack of effect of NFB inhibition on PTGS2 promoter activity in knock-in reporter mice (21). Interestingly, stimulus-induced increases in neuronal COX-2 expression do appear to involve NFB binding.…”
Section: Discussionsupporting
confidence: 91%
“…This expression closely mirrored tissue mRNA levels, with the notable exception of cerebellum and spinal cord, suggesting areas of the promoter that suppress expression may be missing from our construct and/or that native expression in these tissues is influenced by elements in the COX-2 3Ј-UTR. Indeed, underscoring this point, analysis of basal expression of luciferase activity driven from the endogenous PTGS2 gene in a knock-in mouse also shows high expression in cortex and hippocampus, with little expression in cerebellum; the spinal cord was not assessed (21).…”
Section: Discussionmentioning
confidence: 98%
“…COX-2, on the other hand, is hardly detectable in normal conditions but is induced upon stimulation by mitogenic agents, cytokines, growth factors, and so on. Later reports, however, demonstrated that COX-2 is also constitutively expressed in basal levels at several tissues including gastric mucosa, developing brain or kidney [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…COX-2, on the other hand, is hardly detectable in normal conditions but is induced upon stimulation by mitogenic agents, cytokines, growth factors, and so on. Later reports, however, demonstrated that COX-2 is also constitutively expressed in basal levels at several tissues including gastric mucosa, developing brain or kidney [3][4][5].COX isoforms catalyse prostaglandin G/H (PGG2/PGH2) synthesis from arachidonic acid, and these prostaglandins are then converted to stable forms like PGD2, PGE2, PGF2, prostacyclin (PGI2) or thromboxane A2 (TXA2) depending on the cell type. Inhibition of COX enzymes, therefore, could result in improper prostaglandin activity, which in turn may cause diferent side efects.…”
mentioning
confidence: 99%
“…COX-2 expression is induced by inflammatory stimuli, although this enzyme is also expressed constitutively in areas that are not associated with inflammation, including the brain, thymus, gut, and kidney. 1 In the brain, the cerebral cortex shows the highest COX-2 expression. 1 Recent studies have shown that central nervous system COX-2 expression is up-regulated in a variety of neuropathological diseases.…”
Section: Introductionmentioning
confidence: 99%